SISTEM VERIFIKASI SIDIK JARI DENGAN METODE PENCOCOKAN BERBASIS BANK GABOR FILTER - Oka Sudana, A.A. K.; Wiharta, D. M.; Tirta, Mahardhika (Majalah Ilmiah Teknologi Elektro, 2006)
Many cases of fraud are exposed where someone, claiming to be someone else attempts to accesssomething. This situation challenges us to create a system that is both reliable and trustworthy to verify someone’sidentity. A biometric system represent an automatic recognition system based on the physiological characteristicsand/or behaviors of the human being. One of these biometric system is fingerprint recognition. Fingerprint verification system is a system to verify a human fingerprint according to the identity which has been claimed. Thusfingerprint image input is compared with the reference fingerprint image which has been kept in a database,according to the given identity. On this research, the Gabor Filter Bank-based Fingerprint Matching Method is used to extract the image features. On application, one of sample image will be matched with one of the database reference image. First, before matching, the sample image features need to be calculate using the aforementioned method. The resulting matchingprocess will find a reference image which has the shortest Euclidean distance with the sample image. This matchingprocess will only succeed if the sample image and the reference image are from the same person. Images used inthis research are fingerprint images with dimension 191 x 191 pixels. This research is looking for the successful rateand the burst time on the verification process. Result of the system testing show that Gabor Filter Bank Method canprovide high enough success level i.e. 95%. The items influence success level are subject to quality of fingerprint image and accuracy to find a reference point/core point, Similarity between query image and reference image is determined by projection distance both of images, and also threshold value is used to decide whether this image isvalid or not.